New distribution records for Stenoponia americana (Baker) and Stenoponia ponera Traub and Johnson (Siphonaptera: Ctenophthalmidae) with a review of records from the Southwestern United States - Hastriter, Michael W.; Haas, Glenn E.; Wilson, Nixon (Zootaxa, 2006)
The genus Stenoponia is represented in the United States by S. americana (Baker) and S. ponera Traub and Johnson. Stenoponia americana is widely distributed from the eastern seaboard of the United States to the eastern slopes of the Rocky Mountains. The western extreme of S. americana is reported for the first time in Utah, a new state record is given for South Dakota, and additional unpublished records are provided for Arkansas, Colorado, Florida, Georgia, Indiana, Iowa, Kentucky, Montana, New Mexico, and North Carolina. The presence of S. ponera was confirmed in SW Colorado, extending the distribution north by 480 km, additional records are provided for Arizona, and the first record of this species is documented for Texas. A distribution map for Stenoponia in the southwestern United States and a discussion of their ecology is included.